Root dry matter mass and distribution of Florico grass under different grazing strategies - Barros, Ana Carolina Carvalho de; Almeida, João Carlos de Carvalho; Camargo Filho, Sérgio Trabali; Carvalho, Carlos Augusto Brandão de; Campana, Ludmila Lacerda; Morais, Leonardo Fiusa de (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the variations in root dry matter mass (RDM) and the percentage distribution (PD) of the root density of Florico grass (Cynodon nlemfuensis) in the 0–40-cm soil layer, when managed under different grazing strategies. Two defoliation frequencies (90 and 95% light interception, as the criterion for allowing animals in the paddock) and two defoliation severities (post-grazing heights of 20 or 30 cm) were assessed. Four seasonal evaluations of the root system were performed between the winter of 2012 and the autumn of 2013, using the monolith and trench excavation technique, collecting 1-dm3 samples from soil surface down to a depth of 40 cm, in four sequential extracts of 10 cm each. Lower RDM values (0.69 g dm-3) were obtained in winter, with the four grazing strategies, whereas higher values were observed in spring (1.64 g dm-3), for the 30-cm post-grazing residue, and in autumn (1.63 g dm-3) for the 20 cm post-grazing residue, regardless of the light interception value. Between 52 and 66% of the RDM density was observed in the 10-cm layer, for all four grazing strategies, in all seasons.